Hipertensión arterial, factores de riesgo y prácticas de autocuidado en habitantes del Barrio La Vega del cantón Catamayo - Aguilera Sivisapa, María Verónica (2015)
This research entitled "Hypertension, Risk Factors and self-care practices in La Vega neighborhood Inhabitants of Canton Catamayo" was raised in response to the main problem was formulated ¿What are the risk factors and self-care practices in people with Arterial Hypertension of the Vega neighborhood of canton Catamayo during the period July 2014- March 2015? In this direction sought were: to identify the main risk factors in people with arterial hypertension the Vega neighborhood of canton Catamayo; and self-care practices meet holding people with arterial hypertension. A methodology descriptive and cross-sectional research involving everyone connected to the object of research was implemented. The instrument used for data collection was the survey, which the people with arterial hypertension of the Vega neighborhood in canton Catamayo applied. For processing the information the computer program Microsoft Excel, which served for displaying information in tables is used. The results show that the population most affected by high blood pressure is the female, whose age is 66 to 85 years; in relation to inheritance factor a significant percentage of the study group have family members with Hypertension. Lack of physical activity is remarkable in the population and in terms of eating habits predominant fat intake. Self-care practices the highest percentage of the population attends the monthly medical supervision and strictly complies with the pharmacological treatment, but there is a significant percentage do not. KEYWORDS Arterial Hypertension; Non-modifiable risk factors; modifiable risk factors; older adults; self-care practices.